Guidance and Counseling Approach in Overcoming Cyberbullying Among Students - Tasya, Amalia (PT. Anagata Sembagi Education, 2025)
Cyberbullying is a form of digital violence that is increasingly prevalent among students, along with the increasing use of social media and communication technology. The negative impacts of cyberbullying are not only felt emotionally, but can also affect the mental health, academic achievement, and social relationships of victims. This article aims to analyze the Guidance and Counseling (BK) approaches used to address cyberbullying among students. This study uses a qualitative approach with case studies in several junior and senior high schools. The results of the study indicate that BK teachers have a strategic role in providing preventive, curative, and educational services through individual counseling, group counseling, and cross-party collaboration such as teachers, parents, and authorities. In addition, the application of humanistic and cognitive-behavioral approaches has proven effective in helping victims of cyberbullying rebuild self-confidence and develop healthy coping strategies. This article recommends strengthening the capacity of BK teachers and integrating digital literacy into the curriculum as strategic steps for long-term prevention